N-Terminal Plasmodium vivax Merozoite Surface Protein-1, a Potential Subunit for Malaria Vivax Vaccine - Fernanda G. Versiani; Maria E. Almeida; Luis A. Mariuba; Patricia P. Orlandi; Paulo A. Nogueira (Clinical and Developmental Immunology)
The human malaria is widely distributed in the Middle East, Asia, the western Pacific, and Central and South America. Plasmodium vivax started to have the attention of many researchers since it is causing diseases to millions of people and several reports of severe malaria cases have been noticed in the last few years. The lack of in vitro cultures for P. vivax represents a major delay in developing a functional malaria vaccine. One of the major candidates to antimalarial vaccine is the merozoite surface protein-1 (MSP1), which is expressed abundantly on the merozoite surface and capable of activating the host protective immunity. Studies have shown that MSP-1 possesses highly immunogenic fragments, capable of generating immune response and protection in natural infection in endemic regions. This paper shows humoral immune response to different proteins of PvMSP1 and the statement of N-terminal to be added to the list of potential candidates for malaria vivax vaccine.